Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1038/sj.gt.3301370
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant DNA vaccines protect against tumors that are resistant to recombinant vaccinia vaccines containing the same gene

Abstract: Antigen-specific cancer immunotherapy involves the delivery of tumor-associated antigen to the host for the generation of tumor-specific immune responses and antitumor effects. We hypothesized that different delivery systems may influence the pattern of antigen-specific immune response and the outcome of antitumor effect. We therefore evaluated recombinant vaccinia virus and naked DNA for the generation of antigen-specific immune responses and antitumor effects. We previously found that recombinant vaccinia an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…We applied VICE to generate immune-resistant tumor cells in a human papillomavirus (HPV) type-16-associated cervical cancer model, TC-1, which allows us to accurately trace tumor-reactive CTLs based on specificity for the HPV antigen E7 (13). After 3 serial passages, we created TC-1 P3, a derivative of the parental TC-1 line (P0), that is completely impervious to Sig/E7/LAMP-1-based vaccination (1921). …”
Section: Resultsmentioning
confidence: 99%
“…We applied VICE to generate immune-resistant tumor cells in a human papillomavirus (HPV) type-16-associated cervical cancer model, TC-1, which allows us to accurately trace tumor-reactive CTLs based on specificity for the HPV antigen E7 (13). After 3 serial passages, we created TC-1 P3, a derivative of the parental TC-1 line (P0), that is completely impervious to Sig/E7/LAMP-1-based vaccination (1921). …”
Section: Resultsmentioning
confidence: 99%
“…It has also been shown that plasmid vaccines can protect against tumors that are resistant to recombinant vaccinia vaccines containing the same gene. 4 Furthermore, plasmid vaccines can be relatively easily and inexpensively produced and do not require the special handling or storage that some microbial vectors require.…”
mentioning
confidence: 99%
“…The outcome of E7-directed human clinical trials using peptide 11 or recombinant vaccinia viruses expressing E7 and E6 12 as immunogens has been equivocal, although CTL generation was observed in some patients. Although a number of experimental therapeutic vaccines for HPV-associated malignancy has been reported in animal models, (for example, Chu et al, 9 Peng et al, 13 Herd et al, 14 Echchannaoui et al, 15 Daftarian et al, 16 Chen et al 17 ), it is clear that potent strategies readily applicable to humans for inducing CTLs and for priming and boosting anti-tumor responses are necessary, and yet to be developed.…”
Section: Introductionmentioning
confidence: 99%